Proinflammatory Effect of Carbon-Based Nanomaterials: In Vitro Study on Stimulation of Inflammasome NLRP3 via Destabilisation of Lysosomes - Svadlakova, Tereza; Hubatka, Frantisek; Turanek Knotigova, Pavlina; Kulich, Pavel; Masek, Josef; Kotoucek, Jan; Macak, Jan; Motola, Martin; Kalbac, Martin; Kolackova, Martina; Vankova, Radka; Vicherkova, Petra; et al. (Nanomaterials (Basel, Switzerland), 2020)
Carbon-based nanomaterials (C-BNM) have recently attracted an increased attention as the materials with potential applications in industry and medicine. Bioresistance and proinflammatory potential of C-BNM is the main obstacle for their medicinal application which was documented in vivo and in vitro. However, there are still limited data especially on graphene derivatives such as graphene platelets (GP). In this work, we compared multi-walled carbon nanotubes (MWCNT) and two different types of pristine GP in their potential to activate inflammasome NLRP3 (The nod-like receptor family pyrin domain containing 3) in vitro. Our study is focused on exposure of THP-1/THP1-null cells and peripheral blood monocytes to C-BNM as representative models of canonical and alternative pathways, respectively. Although all nanomaterials were extensively accumulated in the cytoplasm, increasing doses of all C-BNM did not lead to cell death. We observed direct activation of NLRP3 via destabilization of lysosomes and release of cathepsin B into cytoplasm only in the case of MWCNTs. Direct activation of NLRP3 by both GP was statistically insignificant but could be induced by synergic action with muramyl dipeptide (MDP), as a representative molecule of the family of pathogen-associated molecular patterns (PAMPs). This study demonstrates a possible proinflammatory potential of GP and MWCNT acting through NLRP3 activation.
Keywords: cathepsin B; graphene platelets; inflammasome NLRP3; THP-1; carbon nanotubes; macrophages